ANALISIS RASIO LIKUIDITAS, LEVERAGE, DAN PROFITABILITAS UNTUK MENGUKUR KINERJA KEUANGAN PADA PT ASTRINDO NUSANTARA INFRASTRUKTUR TBK - Hermawan, Rian; Yanti, Wilda (Universitas Nahdlatul Ulama Kalimantan Timur, 2025)
A company is an organizational entity established to provide products and services to the public, with the primary objective of generating a profit. The Company strives to provide high-quality goods and services, generate a profit while upholding the principles of corporate governance, and support its financial objectives. The purpose of this study was to analyze the economic performance of PT. Astrindo Nusantara Infrastructure Tbk. in managing assets, liabilities, and capital. This research used qualitative methods and analyzed secondary data from the financial reports (balance sheet and income statement) of PT. Astrindo Nusantara Infrastructure Tbk, listed on the IDX from 2018 to 2022. The study employed analysis tools such as the Current & Cash Ratio, Debt to Assets & Equity Ratio, and Return on Assets & Equity Ratio. The company had a poor liquidity ratio during 2018-2022 because the current ratio and cash ratio were below the industry standards of 200% and 50%, respectively. The current ratio was 66.644%, while the cash ratio was only 1.75%. The debt-to-assets and debt-to-equity ratios exceeded the industry standards of 35% and 90%, reaching 64.266% and 192.368%. Meanwhile, the return on assets and return on equity remained below the benchmarks of 30% and 40%, at 1.254% and 3.89%, respectively.